Biomass and carbon stock of conifer and broad-leaf forest stands in Talra Wildlife Sanctuary across Northwest Himalayas, India - Kumar, Anil; Kanwal, Khilendra Singh; Paul, Shiv; Verma, Raj Kumar (Frontiers in Forests and Global Change, 2025)
The Himalayas are a crucial centre of biological diversity, supporting a wide range of habitats of floral and faunal communities. Conserving this ecosystem is vital for sustaining life on Earth, including human well-being. Today, maintaining forest ecosystems in the Indian Himalayan Region (IHR) is indispensable not only for the endemic species, but also for the conservation of global biodiversity. The current study covers Talra Wildlife Sanctuary of northwest Himalaya to quantify the biomass and carbon stock in the conifer and broadleaved forest. The data acquisition was performed through random sampling using 50 × 50 m plots along the different altitudinal gradients. The plants having a diameter at breast height (dbh) >10 cm at a 1.37 girth height were identified, enumerated and measured. The result showed that a total of 14 forest communities were specified based on IVI. The total carbon stock values were found to be varied consistently from 131.5 to 357.7 Mg ha–1 in the TWS. The Picea smithiana-Abies pindrow (Ps-Ap) mixed forest community contained a highest amount of carbon stock, 357.7 ± 48.3 Mg ha–1; followed by Picea smithiana (Ps) and Abies Pindrow (Ap) dominant, respectively. The understory biomass was also found in a range from 2.10 to 4.4 Mg ha–1 (avg. 3.34 ± 0.66Mg ha–1). The litter biomass was in a range of 1.2–2.9 Mg ha–1 (avg. 2.04 ± 0.48 Mg ha–1). Soil properties showed that on the top layer (0–15 cm), soil moisture (%) and soil organic carbon (%) were 30.2 ± 4.7 (%) and 2.9 ± 0.55 (%), whereas 21.3 ± 4.8 (%) and 1.9 ± 0.53 (%), respectively, at a depth of 15–30 cm. The correlation coefficient indicated a positive correlation (r = 0.85; p < 0.05) between tree carbon stock and tree density.